Education and Art: A Possibility of Freedom for Minors in Captivity - García, Vladimir Alberto Pinzón; Díaz, Carlos Alberto Gómez; Ordosgoitia, Leonardo Fabio Abuabara; Patiño, Yudika Aurora Jarque; Bula, Ligia Rosa Martínez (Journal of Ecohumanism, 2024)
This paper seeks to expose the problems experienced in women’s prisons in Colombia, with respect to those who are mothers with loss of liberty. It addresses the right to education of children in captivity and the possibilities that the DIAR programs oriented by the ICBF offer to validate this right, bringing educational strategies to prisons to assist minors in their first three years of life. Likewise, the reflection on the contributions that the development of the arts can offer in educational scenarios other than the institutions created for that purpose is linked, and that, despite the state of captivity of the children, provides exercises of artistic creation, allowing the minors to live freedom in other ways.